2013
DOI: 10.1007/s11605-013-2240-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age on Clinical Outcome of Acute Diverticulitis

Abstract: Younger age is neither associated with a more severe presentation of diverticulitis nor with a higher incidence in recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 15 publications
0
6
1
12
Order By: Relevance
“…Ritz et al demonstrated that clinical presentation and the risk of colonic perforation were not significantly different between the younger and elder patients. In a multicenter study, Ünlü et al found that young age was associated neither with a more complicated presentation nor a higher recurrence rate. In a meta‐analysis Katz et al concluded that the severity of acute diverticulitis was not affected by younger age but tended to recur more often.…”
Section: Discussionmentioning
confidence: 99%
“…Ritz et al demonstrated that clinical presentation and the risk of colonic perforation were not significantly different between the younger and elder patients. In a multicenter study, Ünlü et al found that young age was associated neither with a more complicated presentation nor a higher recurrence rate. In a meta‐analysis Katz et al concluded that the severity of acute diverticulitis was not affected by younger age but tended to recur more often.…”
Section: Discussionmentioning
confidence: 99%
“…demostraron dicho aumento, haciendo énfasis en el aumento significativo de las tasas de ingreso por diverticulitis aguda y en las de colectomía programada en las edades comprendidas entre los 20 a 34 años del 160% y del 126% respectivamente (34) , aunque Ünlü Ç y cols. demostraron que no hay relación entre gravedad o recidiva con respecto a una edad menor de 50 años (12,42) .…”
Section: Factores Precipitantesunclassified
“…Existe un grupo especial de pacientes con riesgo de enfermedad diverticular complicada. Anteriormente los pacientes jóvenes con enfermedad diverticular que por definición se ubicaban en la franja de edad comprendida entre los menores de 40-50 años se les adjudicaba un riesgo más elevado de complicaciones y por lo tanto se recomendaba un tratamiento más agresivo (1,2,12,30,32,42) ; estas recomendaciones se basaban en estudios donde aproximadamente un 48-88% de los pacientes que se les realizaba una intervención quirúrgica por sospecha de diverticulitis, presentaban otro diagnostico postoperatorio.…”
Section: Fisiopatología De La Perforación Diverticularunclassified
See 2 more Smart Citations